A Snapshot on Myxoma Operation of 62 Patients at National Institute of Cardiovascular Diseases(NICVD), Dhaka, Bangladesh - Islam, KS (Bangladesh Heart Journal, 2018)
Background: Intra-cardiac mass, particularly myxoma operation is common at NICVD .Its frequency is about 1-2% among all operations done here. The main aim of this study was to analyze the different aspects of this tumour and its surgery on 62 patients operated over last three years (2015-2017). Methods: It is a retrospective study .The data were collected over a period of 03 years (2015-2017) For this I studied the ward admission register, OT and ICU registers ,ICU flow charts, talked with the respective unit doctors to collect my data. Then the data were analyzed manually and by computer. Results: Age range of the patients were from 7.5 years to 65years with a mean±SD (36.94±13.99). Male and female patient ratio were M:F=1:1.81.Myxoma were more common in the 4th and 5th decade of life in this study population .Preoperative time delay for operation after hospital admission was 9±2.12days.All the operations were done as an elective procedure rather urgent or emergency procedure. Post operative mortality was around 12.90% among these patients. The causes of high mortality following myxoma operation were Low Output Syndrome, Congestive Heart Failure , Cerebral stroke and septicaemia. Conclusion: Myxoma operation is common in NICVD. Most of our patients were dealt as a routine procedure. Their features and surgical procedure were similar with a little difference among the neighbouring countries. Our post operative outcome was a little bit worse (12.90% mortality) over the mentioned period. We need to find out the causes and to take care of these patients to reduce mortality in future. Bangladesh Heart Journal 2018; 33(2) : 85-89